Multiscale analysis of emulsions : a computational fluid dynamics approach (2017)
"Emulsions are thermodynamically unstable colloids composed by immiscible liquids. Due to this instability, its preparation necessitates the addition energy and surfactant agents. These systems are broadly used in diverse industrial applications (e.g. cosmetics, pharmaceutics, food, oil recovery), which suggests that an adequate knowledge of its behavior is of importance. There is, however, a large number of variables that affect the final properties of an emulsion product. Among these variables, disperse phase concentration, continuous phase characteristics and process variables (i.e. mixing velocity, impeller type, etc.) are of special importance. This work have been divided into several chapters for the reason that it is the compilation of two articles previously published in a peer-reviewed journal. Chapter two discusses the methodology implemented for both studies; including the experimental methods as well as the numerical models used during CFD simulations. In chapter three, W/O emulsions are studied with the muñtoscale approximation. In chapter four, O/W emulsions are investigated under a similar methodology."--Tomado del Formato de Documento de Grado.